1990
DOI: 10.1007/bf00232123
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic GUS-like activities in seed plants

Abstract: Fifty-two plant species, covering some Gymnosperms and all the key groups of Angiosperms, were chosen for surveying their intrinsic beta-glucuronidase-like activities. Histochemical (overnight incubation) and qualitative fluorometric (24 h incubation) assays indicated that, with few exceptions, such activities were detected in certain part(s) of the fruit walls, seed coats, endosperms or, especially, the embryos of the tested plants. Most of such activities in the excised immature embryos of soybean and string… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 7 publications
4
39
0
2
Order By: Relevance
“…Subsequent handling of tissue sections (relaxation, binding to microscope slides, solubilization of paraffin with xylene) was performed as described by Schmelzer et al (1 989). Using these methods, endogenous GUS activity, as described in certain floral organs (Plegt and Bino, 1989;Hu et al, 1990), was not observed in any organs examined from untransformed tobacco plants or tobacco plants transgenic for a promoterless GUS gene.…”
Section: Histochemical Localization Of Gus Activitymentioning
confidence: 98%
“…Subsequent handling of tissue sections (relaxation, binding to microscope slides, solubilization of paraffin with xylene) was performed as described by Schmelzer et al (1 989). Using these methods, endogenous GUS activity, as described in certain floral organs (Plegt and Bino, 1989;Hu et al, 1990), was not observed in any organs examined from untransformed tobacco plants or tobacco plants transgenic for a promoterless GUS gene.…”
Section: Histochemical Localization Of Gus Activitymentioning
confidence: 98%
“…Intrinsic GUS activity has been (MCAT) gave no significant changes in the composition and reported in B. napus leaves (Hodal et al 1992) and in mature quantity of storage lipids. However, by use of the seed-specific embryos of B. rapa and B. oleracea (Hu et al 1990).…”
Section: Assessment Of Transgenic Plantsmentioning
confidence: 99%
“…Exposure of humans to the GUS protein is common, because GUS is present in intestinal epithelial cells, intestinal microflora bacteria, and numerous foods, and no harmful effects have been reported (Gilissen et al, 1998). GUS activity has been detected in over 50 plant species (Hu et al, 1990). These species include a number of human food sources, including potato, apple, almond, rye, rhubarb, and sugar beet (Schulz and Weissenbock, 1987;Hodal et al, 1992;Wozniak and Owens, 1994).…”
Section: Characterization and History Of Safe Consumption Of Cry2ab2 mentioning
confidence: 99%